2021
DOI: 10.4149/bll_2021_078
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio, past, present and future perspectives

Abstract: In the review we analyzed short history of the establishment of a novel hematological parameter for systemic infl ammation and stress coined as a neutrophil to lymphocyte ratio (NLR). Today NLR is widely used across almost all medical disciplines as a reliable and easy available marker of immune response to various infectious and non-infectious stimuli. We analyzed the immunological and biological aspects of dynamic changes of neutrophil granulocytes and lymphocytes in circulating blood during endocrine stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
385
2
15

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 355 publications
(413 citation statements)
references
References 32 publications
11
385
2
15
Order By: Relevance
“…The NLR reflects the immune and inflammatory responses more precisely than the total white blood cell (WBC) count [9]. Clinical research confirmed the sensitivity of the NLR for the diagnosis/stratification of systemic infection, sepsis, and bacteremia, as well as its robust predictive and prognostic value [14]. The NLR is predictive of disease severity, septic shock, organ failure, or ICU admission in acute pancreatitis and cholecystitis [9,12,15].…”
Section: Introductionmentioning
confidence: 90%
“…The NLR reflects the immune and inflammatory responses more precisely than the total white blood cell (WBC) count [9]. Clinical research confirmed the sensitivity of the NLR for the diagnosis/stratification of systemic infection, sepsis, and bacteremia, as well as its robust predictive and prognostic value [14]. The NLR is predictive of disease severity, septic shock, organ failure, or ICU admission in acute pancreatitis and cholecystitis [9,12,15].…”
Section: Introductionmentioning
confidence: 90%
“…Moreover, the NLR may serve as a simple haematological parameter for discriminating between bacterial and viral infections since the NLR in bacterial infections is usually higher than that in viral infections [ 11 ]. The NLR improves clinicians’ understanding of systemic inflammation, the pathophysiology of the cellular immune response, and the interaction between innate and adaptive immunity as well as the clinical consequences of disease [ 12 ]. In the present study, the results showed that the SFTS patients in the non-survival group had higher neutrophil counts and lower lymphocyte counts than those in the survival group.…”
Section: Discussionmentioning
confidence: 99%
“…The cut-off values of neutrophil-to-lymphocyte ratio (NLR) to measure the intensity of inflammation were recently refined in line with clinical trials and observations ( 113 ). A normal NLR is about 1–3 ( 114 ), although the values between 2.3 and 3 should be considered as a “gray zone” that reflects latent, subclinical, or low-grade inflammation/stress (NLR 2.3–3.0) ( 27 ). In our study all pre-dive NLR values were below 2.3, whereas all post-dive values were above 2.3 (W1, W3: 2.7; W5: 2.5).…”
Section: Discussionmentioning
confidence: 99%